EFEKTIFITAS KEMASAN ANTIMIKROBA LENGKUAS PADA PEMPEK SELAMA PENYIMPANAN - Yurnalis; Eddwina Aidila Fitria; Tika Rahma Witri (SAGU, 2022)
The purpose of this study was to determine the effectiveness of galangal anti-microbial packaging on the quality of pempek during storage. This study used a simple complete randomized design with 4 levels of treatment and 3 repeats. The treatment in this study was the duration of pempek storage with anti-microbial galangal packaging in the form of edible film for 0, 1, 2 and 3 days. The observational data were analyzed using anova and DNMRT further tests at a real level of 1%. The results showed that the duration of pempek storage with antimicrobial galangal packaging significantly affected moisture and, protein contents as well as the amount of mold. Antimicrobial packaging of galangal is less effective in inhibiting mold growth. The growth of mold still occured until the third day by number of 3,0x104 CFU/g.